Comorbidity between psychosis and eating disorders: a systematic review - Oliver Rumle Hovmand; Linda Lloyd Hughes; Celeste Mary Egtved; Sidse M. Arnfred (Journal of Eating Disorders)
Abstract Background Comorbidity has been reported between eating disorders and psychotic illnesses such as schizophrenia, and several hypotheses regarding their relationship have been proposed. Therefore, we aimed to systematically review studies involving patients who are affected by both psychotic symptoms and eating disorders (ED). Method We systematically searched three databases for all studies describing psychotic symptoms among patients diagnosed with eating disorders. We conducted and reported the systematic review following the PRISMA statement. Results We included 67 publications, of which 41 were case reports and 26 were descriptive studies. Most of the included studies described transient psychotic symptoms among individuals with ED or suggested comorbidity between schizophrenia and anorexia nervosa. Discussion The included studies were highly heterogeneous. The review suggests at least three different patterns of psychopathology: 1) patients with anorexia nervosa who experience transient psychotic symptoms in correlation with severe mental or physical stress; 2) patients suffering from comorbid schizophrenia and anorexia nervosa and fulfilling diagnostic criteria for both diagnoses; and 3) patients with psychotic illness who are experiencing disordered eating as part of their psychotic illness, but do not fulfill diagnostic criteria for it. Future research could conduct psychopathological follow-up on patients enrolled in treatment for these conditions.